The Biomedical EDP User—his Expectations and Impressions from the Use of Terminals - Pilgrim, J. (Methods of Information in Medicine, 1982)
Having outlined the problems and characteristics of the user’s attitude toward EDP, results are presented attempting to assess the effects of display-oriented computer use by biomedical staff. Expectations and real effects of terminal use obtained from three different user groups have been taken as a basis. The mental and physical load experienced by them and factors of personality are discussed, and conclusions are drawn. It has become evident that the design of communicative relations is essential for more effective EDP use in biomedical research.
Keywords: Biomedical EDP User; Behaviour; Terminal Use; Personality Factors; Factors of Mental and Physical Stress